Mathematical models for evaluation of operational readiness of periodically inspected electronic systems - Ulansky, V.V.; Machalin, I.A. (Математичні машини і системи, 2012)
The mathematical models and theorems that identify stationary and non-stationary coefficients of operational readiness are developed for an arbitrary and exponential distribution of time to failure of avionics systems. Proven expressions, in contrast to all other known, take into account the trustworthiness characteristics of multiple inspections. It is shown that the mean time between unscheduled repairs of the system is largely determined by the probability of a false failure. Розроблено математичні моделі та доведено теореми, що дозволяють визначити стаціонарний і нестаціонарний коефіцієнти оперативної готовності при довільному і експоненційному законах розподілу напрацювання системи до відмови. Доведені вирази, які, на відміну від відомих, враховують характеристики достовірності багаторазового контролю працездатності. Показано, що середній час напрацювання на незапланований ремонт системи багато в чому визначається ймовірністю помилкової відмови. Разработаны математические модели и доказаны теоремы, позволяющие определить стационарный и нестационарный коэффициенты оперативной готовности при произвольном и экспоненциальном законах распределения наработки системы до отказа. Доказанные выражения, в отличие от известных, учитывают характеристики достоверности многократного контроля работоспособности. Показано, что среднее время наработки на незапланированный ремонт системы во многом определяется вероятностью ложного отказа.